Poorer Subjective Sleep Quality Is Related to Higher Fantasy-Induced Sexual Arousal in Women of Reproductive Age. Issue 8 (16th November 2016) - Costa, Rui M.; Oliveira, Tânia F.
Abstract : Lack of sleep enhances erections and lubrication the next day. This raises the possibility that poorer subjective sleep quality is related to sexual arousal. To test this hypothesis, sexual arousal was elicited in 70 Portuguese women of reproductive age by means of fantasy. The level of salivary testosterone before and shortly after fantasy was determined by luminescence immunoassays. Participants completed the Pittsburgh Sleep Quality Index (PSQI), reported their sexual arousal before and during fantasy, and how anxious they were after the fantasy. The hypothesis was confirmed. Anxiety did not explain the association, but testosterone response (poststimulus minus baseline) had a slight explanatory effect.